Bioinspired Fabrication of High‐Quality 3D Artificial Compound Eyes by Voxel‐Modulation Femtosecond Laser Writing for Distortion‐Free Wide‐Field‐of‐View Imaging. Issue 8 (24th June 2014) - Wu, Dong; Wang, Jian‐Nan; Niu, Li‐Gang; Zhang, Xu Lin; Wu, Si Zhu; Chen, Qi‐Dai; Lee, Luke P.; Sun, Hong Bo
<x xml:space="preserve">Abstract</x> The small field‐of‐view (FOV) limits the range of vision in various detecting/imaging devices from biological microscopes to commercial cameras and military radar. To date, imaging with FOV over 90° has been realized with fish‐eye lenses, catadioptric lens, and rotating cameras. However, these devices suffer from inherent imaging distortion and require multiple bulky elements. Inspired by compound eyes found in nature, here a small‐size (84 μm), distortion‐free, wide‐FOV imaging system is presented via an advanced 3D artificial eye architecture. The 3D artificial eye structure is accomplished by exploiting an effective optical strategy — high‐speed voxel‐modulation laser scanning (HVLS). The eye features a hexagonal shape, high fill factor (FF) (100%), large numerical aperture (NA) (0.4), ultralow surface roughness (2.5 nm) and aspherical profile, which provides high uniformity optics (error < ±6%) and constant resolution (FWHM = 1.7 ± 0.1 μm) in all directions. Quantitative measurement shows the eye reduces imaging distortion by two/three times under 30°/45° incidence, compared with a single lens. The distortion‐free FOV can be controlled from 30° to 90°.